Organic‐inorganic‐hybrid‐enhancement Electrochemical Sensor for Determination of Cu (II) in River Water. Issue 8 (18th April 2018) - Wu, Ju; Chen, Xin; Wang, Qishai; Bian, Yuting; Zhang, Kai; Sheng, Zhong; Jin, Juncheng; Yang, Mei; Dai, Panpan; Fu, Xucheng; Chang, Wengui; Xie, Chenggen
Abstract: A dual strategy that the L‐cysteine self‐assembling on three‐dimensional network of organic‐hybrid‐materials realized by successive interaction of Au−S bond is employed to construct as the amplified electrochemical sensor for determination Cu (II). Specifically, the sensor combined a rigid three‐dimension inorganic net which provides a higher interfacial area as well as faster adsorption of ions. Accordingly, surface and interfacial‐dominated electro‐catalysis reactivity is used as an ideal test‐bed to verify the reliability of electrochemical sensor that reveal enhancement sensitiveness and selectivity, low detection limit, and stability over a long period of time. Time‐dependent density functional theory (TD‐DFT) were used to calculating the all complexes energies at the B3LYP/LANL2DZ level associated with the polarized continuum model (PCM). The result of calculation indicates that the binding strength of Cu (II), Cd (II), As (III), Hg (II) with L‐cysteine are decrease successively, and this is in well agreement with experimental results. This work not only achieves an unprecedented understanding to L‐cysteine/Au/TiO2 /GCE sensor but also provides a new perspective for application in detection of Cu (II) in real river waters. Abstract :